Podręczniki do systemów klasycznych gier fabularnych jako gatunek (próba rekonstrukcji wzorca) - Matyka, Marzena (Słowo. Studia językoznawcze, 2012)
Classical role-playing games (classical RPG) are the games based on imagination and performance. They are meant for a group of players and so-called Game Master. The Game Master is the storyteller of a plot that takes place in a fictional universe. Every player imagines a character settled in that world, decides his/her actions and plays his/her role. The rules that settle a behaviour of characters and functioning of the game world (understood as a system) are described in special guidebooks. This article is considered an attempt to depict classic role-playing games” guidebooks as a realization of a pattern of the genre. The analysis is concerned with pragmatic, structural, cognitive and stylistic aspects of the references that allowed to reconstruct the canonical genre pattern of classic role-playing games” guidebook.